H.G. Wells In The Reception of E.I. Zamyatin (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article deals with the peculiarities of E.I. Zamyatin's perception of H. Wells' work. Zamyatin considered H. G. Wells as his creative predecessor, who had a great influence on the formation of the fantastic novel as a genre combining acute plot with social analysis of the consequences of scientific and technical development. The author of the novel ‘We’ notes the anti-utopianism of many of H.G. Wells' novels and connects it with the opposition “static utopia - dynamism of anti-utopia”. Zamyatin's attitude to the realistic work of Wells is more restrained. Wells is perceived by Zamyatin as a deeply national writer, aware of his national identity, rooted in the Dickensian tradition and reflecting in his work the peculiarities of the English mentality. The created myth of the English writer becomes at the same time a projection of Zamyatin's own aesthetic programme of the early 1920s, developed in other articles and lectures of the writer of this period.